Neonatal mastitis: Case series in a neonatal intermediate care unit - Parreira de Andrade, Beatriz (2023)
Neonatal mastitis is a rare infection of the breast tissue in the newborn. In most cases, it presents unilaterally in the third week of life and has a favorable prognosis. The treatment of choice remains controversial. The aim of this study was to retrospectively review the cases of neonatal mastitis diagnosed and treated in a neonatal intermediate care unit between July 2000 and June 2020. Ten female neonates with neonatal mastitis were included in the study. The mean age at diagnosis was 22 days. All cases presented with unilateral mastitis and no systemic signs. Staphylococcus aureus was isolated in six cases and was methicillin-resistant in two. Neonates were predominantly treated with intravenous flucloxacillin for a median of 10 days. Four cases presented abscesses, three of which were surgically drained. All infants had a favorable outcome. The present cases of neonatal mastitis showed similar characteristics to those reported in the literature, namely a higher incidence in females, unilateral presentation, and association with Staphylococcus aureus infection. The authors propose an algorithm for the prompt diagnosis and treatment of this condition, ensuring favorable outcomes by minimizing the risk of sepsis and breast tissue sequelae.